Penerapan Metode Demonstrasi dalam Meningkatkan Motivasi Belajar Siswa pada Pelajaran Fikih di MI Al-Mukhlisin Jurumudi Tangerang - Neneng Sholiha; Eka Naelia Rahmah (Fakultas Tarbiyah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2022)
The purpose of this study was to find out how the application of the demonstration method could increase students' learning motivation in fiqh lessons at MI Al-Mukhlisin Jurumudi Tangerang. And also to train students' mentality, develop knowledge and ideas in the surrounding environment. The type of research that the author carries out is qualitative, using the methods of observation, interviews, and documentation, and also uses technical data analysis, namely data reduction, data presentation, and drawing conclusions.The results of the study In the application of the demonstration method at MI Al-Mukhlisin Jurumudi Tangerang it has been carried out well and greatly helps students in understanding and facilitating the fiqh learning process, and also students can increase student motivation. high enthusiasm, students become independent, and happy to have an opinion. Based on this, the application of this demonstration method can increase student learning motivation at MI Al-Mukhlisin Jurumudi Tangerang.